Orneal biomechanical changes following femtosecond lasik and femto smile : a comparative study - Ahmed Tarek Ahmed Othman; Ahmed Mostafa Abdelrahman; Dina Mohamed Said El-Fayoumi; Hany El-Mekkawy (Cairo : Ahmed Tarek Ahmed Othman, 2017)
Corneal refractive surgery performed by excimer laser has matured considerably and was able to cover from +6 to {u2212}12 diopters of sphere and up to 6 diopters of astigmatism with good, predictable and safe outcomes p(3)(4)(B. Hyperopia had been one of the frontiers approached with caution by modern corneal refractive surgeons, but evidence had confirmed its feasibility for up to 7 diopters with acceptable induction of high order aberrations (HOA), equivalent to those induced by previous generations of excimer laser corneal surgical devices in hyperopic corrections up to +3 spherical diopters p(5)s
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Ophthalmology
Issued also as CD
Keywords: Corneal surgery; Femtosecond lasik; Outstanding innovations